Faktor-Faktor Yang Mempengaruhi Guru Menggunakan Lembar Kerja Anak (LKA) Dalam Pembelajaran Di TK Pertiwi - Florentina Ina Lewowerang; Sartika Kale; Fredik Lambertus Kollo; Gokma N. Tampubolon (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Children's Worksheets (LKA) are commonly used learning media in Early Childhood Education (PAUD) because they are considered practical. However, their dominant use has the potential to limit learning variations and children's exploration. This study aims to analyze the factors influencing teachers' use of LKA at TK Pertiwi, Kupang City. The approach used is descriptive qualitative with observation, interviews, and document studies. , as well as data validity through technical triangulation and source triangulation. The research informant were the principal, the B1 class teacher, and the B2 class teacher, who are directly involved in the use of LKA. The data analysis technique used the Miles and Huberman model, which includes data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that teachers' use of LKA is influenced by two main factors: internal and external factors. Internal factors include teachers' skills in using LKA and teachers' teaching motivation, while external factors include parents' responses to the use of LKA. The use of LKA by teachers is based on considerations of practicality, ease of classroom management, and its effectiveness in supporting the smooth learning process. Thus, efforts are needed to develop more varied learning media in order to optimally meet the developmental needs of early childhood.